Curvi-linear shear strength envelope for residual soil in precinct 9, Putrajaya for unsoaked and soaked multistage triaxial drained test / Abdul Samad Abdul Rahman - Abdul Rahman, Abdul Samad (2012)
To determine the mode of slope failures is very difficult especially when using the conventional slope stability method which applies the linear type of strength variation with respect to effective stress and suction. These studies were conducted to fulfil the real failure mechanism of slope failure which included the analysis of shear strength behaviour incorporating curvi-linear relative to effective stress and non-linear relative to suction. Three undisturbed samples were collected at Precinct 9, Putrajaya at different depths to determine the multistage triaxial drained tests with unsoaked, soaked for 7 days and soaked for 14 days samples. Findings show that from the test, there were slight reductions in shear strength between all the samples. For unsoaked sample, the shear strength was 28°, , soaked for 7 days was 25° and for soaked for 14 days was 22°. The shear strength parameters obtained from the results will be used in slope stability analysis in order to define the Factor of Safety for slope failure.